The Effectiveness of Using Flipbook-Based Digital Media to Improve Student Digital Literacy - Yunita Tria Saputri; Ratnasari Diah Utami (Universitas Muhammadiyah Surakarta, 2025)
Purpose: Digital literacy is a key competence that must be developed from an early age, particulary at the elementary school level in the digital era. This study aims to examine the effectiveness of flipbook-based digital media in improving the digital literacy skills of fourth grade students at SD Negeri Trosemi 02.Methodology: All 17 fourth-graders chosen by total sampling participated in the study's quantitative preexperimental one-group pretest and posttest design. To assess the efficacy of flipbook media in enhancing digital literacy, data were gathered through interviews, observations, tests, and documentation. Validity and reliability tests, descriptive statistics, normality testing, and a paired sample t-test were used for analysis.Results: Research results show that the use of flipbook media has a positive and significant influence on improving students' digital literacy skills. This proves an average increase of around 18,07 points, from a pretest average value of around 50,42 to 68,49 in the posttest. Student’s digital literacy skills before and after using flipbook media change significantly, according to the Paired Sample T-Test results, which show a significance value of 0.000 < 0.05.Applications/Originality/Value: This study provides empirical evidence that flipbook-based digital media is an effective learning innovation for improving the digital literacy of elementary school students and supporting 21st-century competencies. Its main contribution is to show that flipbooks serve as a simple but highly impactful digital learning tool in basic education.